GEOMETRI JALAN ANGKUT TAMBANG PADA KP PT. INDONESIA TIMUR RAYA NABIRE – PAPUA - Jance M. Supit (Jurnal Natural, 2007)
Haul road is an important infrastructure that functions as places connector in mining area. In as much, it is necessary to make haul road geometry plan that suitable to the equipments and mining location. The study of mining haul road conducted in 200 Ha of PT. Indonesia Timur Raya mining area. The study methods are by observation on road site and calculation to decide the haul road geometry, including road wide and slope. The equipment that will be used is wheel loader XCMG ZL50G, from the calculation base on the wheel loader specifications, the minimum haul road wide is 10.5 meters for straight road and 28 meter in curve road.